2020
DOI: 10.1007/s12975-020-00797-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Progressive Changes in White Matter Integrity Are Associated with Stroke Recovery

Abstract: Information on microstructural white matter integrity has been shown to explain post-stroke recovery beyond clinical measures and focal brain damage. Especially, knowledge about early white matter changes might improve prediction of outcome. We investigated 42 acute reperfused ischemic stroke patients (mean age 66.5 years, 40% female, median admission NIHSS 9.5) with a symptomatic MRI-confirmed unilateral middle cerebral artery territory infarction 24–72 h post-stroke and after 3 months. All patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Compared to neurologically intact controls, chronic stroke survivors showed significant reduction in FA across the genu (CC1) and body (CC 2, 3, 4) of the corpus callosum, but no difference was found in the splenium (CC5). We extended previous findings of lower callosal FA in acute stroke (Pinter et al, 2020) survivors to the chronic phase, in those with mild to moderate motor impairment (Hayward et al, 2017;Stewart, Dewanjee, et al, 2017), and in pediatric hemiplegia (Hawe et al, 2013). Given that the CC was not directly lesioned (as demonstrated by < 0.05% of overlap between the lesion and the CC), the reduction in FA across the CC is evidence for transcallosal diaschisis.…”
Section: The Effects Of Stroke On CC Regions Connecting the Larger Sensorimotor Networksupporting
confidence: 72%
“…Compared to neurologically intact controls, chronic stroke survivors showed significant reduction in FA across the genu (CC1) and body (CC 2, 3, 4) of the corpus callosum, but no difference was found in the splenium (CC5). We extended previous findings of lower callosal FA in acute stroke (Pinter et al, 2020) survivors to the chronic phase, in those with mild to moderate motor impairment (Hayward et al, 2017;Stewart, Dewanjee, et al, 2017), and in pediatric hemiplegia (Hawe et al, 2013). Given that the CC was not directly lesioned (as demonstrated by < 0.05% of overlap between the lesion and the CC), the reduction in FA across the CC is evidence for transcallosal diaschisis.…”
Section: The Effects Of Stroke On CC Regions Connecting the Larger Sensorimotor Networksupporting
confidence: 72%
“…The values of nodal efficiency in the right postcentral gyrus and right IPL were also enhanced one month later in stroke patients. Previous studies have found a beneficial role of motor-related areas on the recovery of motor function following stroke [ 7 , 51 , 52 ]. Additionally, the connectivity related to these motor-related areas was improved and tended toward connectivity values of healthy participants after clinical intervention [ 11 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion MRI measures on white matter (WM) integrity in stroke have found that patients showed a significant decrease of WM integrity in the hemisphere at an early stage. The decreased WM integrity showed further reduction over 3 months compared with healthy controls [ 7 ]. Regional variability in stroke patients demonstrated cortical thickness increases particularly in contralesional paracentral, superior frontal and insular regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we assessed in vivo DTI as a neuroimaging biomarker for WM and GM integrity 1 week after tMCAO in the same and additional ROI that were used for CBF analysis. WM degeneration after ischemic stroke is associated with reduced fractional anisotropy (FA) and increased mean diffusivity (MD) (Wiesmann et al, 2017(Wiesmann et al, , 2018Pinter et al, 2020).…”
Section: Brain Structure and Functionmentioning
confidence: 99%